Tcf1 and Lef1 pack their own HDAC - Ng, Charles P (Nat Immunol, 2016)
The transcription factors Tcf1 and Lef1 have intrinsic histone-deacetylase activity that is required for the repression of CD4(+) T cell-lineage genes in CD8(+) T cells.